Ferromagnetic Ising chains in frustrated LnODCO3: the influence of magnetic structure in magnetocaloric frameworks. Issue 42 (8th October 2019) - Dixey, Richard J. C.; Stenning, Gavin B. G.; Manuel, Pascal; Orlandi, Fabio; Saines, Paul J.
Abstract : Understanding how to tune magnetic interactions to optimise the magnetocaloric effect is crucial for designing more efficient solid state refrigerants; this work probes this relationship for the promising LnODCO3 phases. Abstract : Probing the magnetic interactions in functional magnetic materials can reveal detailed insight into how to optimise the properties they possess while providing key understanding of the exotic phenomena they may host. This study probes the short and long range magnetic order in the LnODCO3 (where Ln = Tb, Dy, Ho, and Er) framework magnetocalorics using variable-temperature neutron scattering measurements. Reverse Monte Carlo analysis of neutron scattering data shows that TbODCO3, DyODCO3 and HoODCO3 develop short range Ising-like magnetic order between 1.5 and 20 K, consistent with dominant ferromagnetic correlations within chains along the b -axis. Through magnetic susceptibility measurements we identify that long range magnetic order develops in TbODCO3 and HoODCO3 at ∼1.2 and ∼0.9 K, respectively. Neutron diffraction measurements were conducted on HoODCO3 revealing incommensurate magnetic order develops between 1.2 and 0.9 K, before a commensurate magnetic phases emerges at 0.8 K with long-range ferromagnetic order in the chains. The results suggest Ising-like ferromagnetic chains associated with frustration are responsible for the improved magnetocaloric properties, of some members in this family, at higher temperatures and low applied fields.